ANALISIS KEGIATAN BELAJAR OFFLINE DAN ONLINE PADA SISWA KELAS 9 MTsN 4 BOJONEGORO DI ERA PANDEMI COVID-19 - Putriyana Permata Sari Kuraesin; Nafis Fahira; Alvina Khurriyatul Afdillah; Fatmah Fatmah; Ita Ainun Jariyah (Program Studi PGSD Universitas Flores, 2022)
The Covid-19 pandemic that hit the world, including Indonesia, stopped activities in all fields, especially education. The government has implemented a policy that learning activities must be carried out online to prevent the spread of the virus. The easing of the pandemic makes offline learning then re-applied even within certain limits. The purpose of this research is to analyze the comparison of online and offline teaching and learning activities in 9th graders at MTsN 4 Bojonegoro. The method used is qualitative descriptive with survey techniques. The results showed that 74.2% preferred offline learning systems. Online learning is considered to have many obstacles, such as lack of understanding of learning materials, limited internet network, the use of high internet data, problematic the implementation of midterm exam or final exam, to the difficulty of concentrating due to disruption from the home environment. A total of 66.1% of respondents stated that teachers could not convey materials and communicate effectively in online learning, and 54.8% of respondents stated the difficulty of communication between learners online. Respondents also assessed that understanding of the material could work well in offline learning (54.8%) and considered the work on the task would be easier if the learning was done offline (66.1%), than when done online.